Case report: Spontaneous remission of synchronous endometrial and ovarian cancers following pregnancy - Daley, Diandra; Padwick, Malcolm; Mistry, Sabina; Malhotra, Vivek; Vikram, Radhika Selvi; Stanciu, Paul (Frontiers in Oncology, 2022)
Introduction Endometrial cancer is one of the most common malignancies affecting women. It is uncommonly diagnosed in young women, particularly in the absence of abnormal vaginal bleeding symptoms. Case presentation A 28-year-old woman was referred to our department with lower abdominal pain. Transvaginal ultrasound showed a complex right adnexal mass with mixed echogenicity. Magnetic resonance imaging (MRI) identified a right-sided, torted, cystic solid ovarian mass, and a polypoid lesion in the uterine cavity. Diagnosis Following multidisciplinary team advice, hysteroscopic transcervical resection of endometrial polypoid mass and laparoscopic right salpingo-oophorectomy was performed. Histopathologic assessment of the endometrial tissue showed changes consistent with grade 1 endometrioid endometrial carcinoma, while the right ovarian mass showed a well-differentiated endometrioid carcinoma. Intervention The patient underwent hormonal treatment and surveillance whilst making a final decision regarding further surgical management. However, the patient stopped hormonal treatment after 2 weeks, went abroad and absconded from treatment for 8 months. On her return, she had conceived naturally and was in the first trimester of pregnancy. Further management was postponed until the patient was 7 weeks postnatal. The patient was not keen on any further surgical management and opted for close surveillance with ultrasound scans and hysteroscopies with endometrial biopsies. All subsequent endometrial biopsies showed normal endometrium, with no evidence of hyperplasia or malignancy. Outcome To date, the patient remains on a 6-monthly surveillance plan and is considered to have had complete natural remission of her endometrial and ovarian cancers following pregnancy. Conclusion This unique case demonstrates a natural phenomenon, in which the complete, natural remission of endometrial and ovarian cancers occurred following pregnancy and childbirth. The aetiology may be related to the high progesterone levels occurring in pregnancy.